Synthesis of Research on Science Learning Management Affecting Problem Solving Skills: Meta-Analysis - Thanatcha Sainapha; Thanin Ratanaolarn; Krissana Kiddee (International Journal of Instruction, 2024)
The rapidly changing world of the 21st century is complex and unpredictable. The researcher aimed to study the findings from a meta-analysis of 42 research studies related to the learning management of science that affects problem-solving skills during 2012–2022 from a database in Thailand called ThaiLIS. The findings revealed the variables that cause different mean effect sizes and the influence of research quality on the effect size. The instruments of this research were the research quality assessment form and the research characteristics assessment form. Statistics for data analysis were mean, standard deviation, one-way analysis of variance, and multiple regression analysis. The directional research hypothesis, multi-stage sampling, randomized control group post-test only design, PBL, and Weir's solution theory were discovered in the study to be the variables that caused the mean effect sizes to differ at the statistical significance level of .05. In addition, research quality had a positive influence on the effect size. The findings of this study will be useful to teachers who want to provide learning management of science that helps students develop problem-solving skills. This will develop skills more effective than traditional teaching.
Keywords: Technology-Enhanced Education Studies